Hormone-Like Activities of Humic Substances in Different Forest Ecosystems - Pizzeghello, Diego; Nicolini, Gianni; Nardi, Serenella (The New phytologist, 2002)
• In order to understand the phytohormone-like activity of humic substances (HS) with respect to vegetation, different forest ecosystems were considered. For this study, 32 soil horizons from a large area of northern Italy typical for silver fir (Abies alba) were evaluated. • The development of organic and humic matter in the five silver fir forest types was assessed by quantifying chemical and biochemical parameters. Phytohormone-like activity of HS was evaluated by measuring auxin-like (indoleacetic acid (IAA)-like) and gibberellin-like (GA-like) activities as well as invertase and peroxidase activities. • Differences between ecosystems were obtained by comparing the five silver fir types with previous work in beech forests, which investigated three large groups: thermophilous, mesophilous and acidophilous. In these eight forests it was reconfirmed that acid conditions were essential for the release of the IAA-like activity, whereas neutral conditions promoted GA-like activity. • Humic substances are of ecological importance because their phytohormone-like activity stands out not only within the five silver fir forest types, but also between the silver fir and beech types. Our results demonstrated a different collocation of the hormone-like activity along the profile in accordance with the different growth conditions, seed germination and the first stage of seedling growth. Humic substances evoke the greatest response on seed germination and on the first stage of seedling growth, particularly in stressed environmental conditions.